Staffing for results : - Mayo, Diane (American Library Association, 2002)
The PLA Results series has a new title that offers ways to measure performance and output to improve work processes and efficiency. With common public library tasks as the basis for discussion, the guide shows managers and staff how to define terms to measure work, assess performance, review and realign staff, redesign processes, and create meaningful communication. The step-by-step chapters, case studies, examples, charts, and forms provide direction to managers and staff, both neophytes and seasoned librarians.